Protection of Children and Teenagers in the Audiovisual Media System in Poland in from the Perspective of European Solutions (Archives of Criminology, 2008)
This article discusses legal regulations on the protection of children and young people from the harmful influence of mass media. It points out their increasing socialising role, in shaping young people’ssystem of values and attitudes to life. The text presents documents which contain international standards on the protection of minors, citing the Convention on the Rights of the Child of 1989, the Convention on Transfrontier Television of the Council of Europe, and the Directive of the Council of the European Communities on Television without Frontiers. These provisions regulate the issues of disseminating indecent content and specify the broadcasting hours when children and adolescents would be denied access to it. The author also refers to the Polish Broadcasting Act of 1993 and the regulations contained therein, such as the introduction of a watershed in the evening hours. The regulation of the National Broadcasting Council discussed in the text also had a significant impact on the protection of children and young people from the harmful influence of audio-visual media. The article analyses the conducted amendments to the Television without Frontiers Directive and the Convention on Transfrontier Television, which serve to oblige the Member States to ensure the safety of content presented by the operating mass media. As an example of such action, the text refers to the Friendly Media Agreement signed by broadcasters in 1999, thanks to which a uniform system of labelling broadcast programmes was introduced; the text provides a detailed description of the symbols introduced. Badźmirowska-Masłowska analyses in detail the provisions of the new directive from 2007 on audio-visual services (AMSD), under which the progressive technological revolution was given as an argument to introduce changes. In the conclusion, the author expresses the need to create universal regulations due to the global nature of the Internet and close cooperation of the governmental, private, and social sectors in this field. The article also stresses the important role of media education leading to raised awareness of the opportunities and threats resulting from the content featured on the Internet and in the media.